2003
DOI: 10.1186/1471-2334-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Determination of decimal reduction time (D value) of chemical agents used in hospitals for disinfection purposes

Abstract: Background: Prior to the selection of disinfectants for low, intermediate and high (sterilizing) levels, the decimal reduction time, D-value, for the most common and persistent bacteria identified at a health care facility should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 9 publications
4
63
0
4
Order By: Relevance
“…Several CECMEL11 antifungal peptides have been found to be sporicidal against F. oxysporum and P. expansum at concentrations around the MIC. Notably, the best peptides killed 99 to 99.9% of the F. oxysporum spores in 35 min at 20 M. These results correspond to decimal reduction times of 10 to 15 min, which are comparable with the ones reported for currently used antiseptics and disinfectants (30). Moreover, the correlation observed between sporicidal activity and Sytox green uptake suggests that fungal membrane disruption could be the primary mode of action.…”
Section: Discussionsupporting
confidence: 73%
“…Several CECMEL11 antifungal peptides have been found to be sporicidal against F. oxysporum and P. expansum at concentrations around the MIC. Notably, the best peptides killed 99 to 99.9% of the F. oxysporum spores in 35 min at 20 M. These results correspond to decimal reduction times of 10 to 15 min, which are comparable with the ones reported for currently used antiseptics and disinfectants (30). Moreover, the correlation observed between sporicidal activity and Sytox green uptake suggests that fungal membrane disruption could be the primary mode of action.…”
Section: Discussionsupporting
confidence: 73%
“…Treatment efficiency can be proved by the release of DPA to the suspension after the alkaline treatment and TEM observations. It has been previously reported that inactivation of G. stearothermophilus at low temperatures (<100 o C) can be achieved using chemicals agents (Mazzola et al, 2003;Rogers et al, 2007), high-pressure carbon dioxide (Watanabe et al, 2003) and supercritical carbon dioxide with added hydrogen peroxide (Hemmer et al, 2007) but the time required to inactivate spores is high. The D-values found in literature for inactivation assays carried out at temperature 100 o C were higher than those obtained in this work (Table S1), except when using high pressure treatments (Patazca et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To be able to put a value to biocide activity, two measures have been used, the D and E values. The D value is the time taken to reduce a population of indicator organisms either in suspension or attached to a surface (carrier test) by 90% (126). For instance, the D value of 0.025% sodium hypochlorite at pH 7 against E. coli is 6.1 min (126).…”
Section: Biocidesmentioning
confidence: 99%
“…The D value is the time taken to reduce a population of indicator organisms either in suspension or attached to a surface (carrier test) by 90% (126). For instance, the D value of 0.025% sodium hypochlorite at pH 7 against E. coli is 6.1 min (126). Carrier tests are considered to be a more appropriate measure of biocide activity; these are tests in which the bacteria are attached to a surface, often after formation of a biofilm, and are considered to be less susceptible to antimicrobial compounds than bacteria grown in suspension (109).…”
Section: Biocidesmentioning
confidence: 99%